Pengaruh ROE, DER, CR, TATO, dan DPR terhadap PBV pada Perusahaan Manufaktur Subsektor Food and Beverage yang Terdaftar di BEI Periode 2020–2024 (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), Total Asset Turnover (TATO), and Dividend Payout Ratio (DPR) on Price Book Value (PBV). The population of this research consists of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was determined using a purposive sampling technique, resulting in 18 companies with a total of 90 data observations. This research employs a quantitative approach with secondary data. The analysis technique used is multiple linear regression. The findings indicate that Return on Equity (ROE) has a significant effect on Price Book Value (PBV), Debt to Equity Ratio (DER) also has a significant effect on Price Book Value (PBV), while Current Ratio (CR), Total Asset Turnover (TATO), and Dividend Payout Ratio (DPR) have no significant effect on Price Book Value (PBV).